Efektivitas Penerapan Pembiayaan Musyarakah Pada Baitul Maal Wa Tamwil (BMT) Bima Kota Magelang - Fadlillah, Mauliya Nur; Khotijah, Siti Afidatul (IAIN Kudus, 2021)
The purpose of this study was to determine the effectiveness of the profit-sharing Musyarakah financing procedure at BMT BIMA Magelang. This study is a qualitative research, uses field research. Data collection techniques through interviews, documentation, and observation, while data analysis techniques using descriptive analysis techniques. The results of the study found that the Musyarakah financing procedure at BMT BIMA Magelang has been carried out effectively because it has carried out the financing process according to sharia principles and provisions, namely, an ijab qabul process between the customer and the BMT, the parties who make contracts, an object of the capital agreement, and a transparent ratio distribution of profits and losses. This study shows that for every increase in the use of Musyarakah financing, there is also an increase in the income of BMT BIMA Magelang.